2015
DOI: 10.1002/2015ja021063
|View full text |Cite
|
Sign up to set email alerts
|

Heavy‐ion dominance near Cluster perigees

Abstract: Time periods in which heavy ions dominate over H+ in the energy range of 1–40 keV were observed by the Cluster Ion Spectrometry (CIS)/COmposition DIstribution Function (CODIF) instrument onboard Cluster Spacecraft 4 at L values less than 4. The characteristic feature is a narrow flux peak at around 10 keV that extends into low L values, with He+ and/or O+ dominating. In the present work we perform a statistical study of these events and examine their temporal occurrence and spatial distribution. The observed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 93 publications
(158 reference statements)
7
36
0
Order By: Relevance
“…Drifting plasma sheet ions are energized by the increased magnetic field strength (as well as temporarily energized by field fluctuations). Aging of the drifting plasma over a~24 h period led to an enhanced heavy ion content [Smith and Bewtra, 1978;Fok et al, 1991;Ebihara et al, 1998;Ferradas et al, 2015;Kistler and Mouikis, 2016]. This plasma mimics the presence of local in situ acceleration of the low-energy population.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Drifting plasma sheet ions are energized by the increased magnetic field strength (as well as temporarily energized by field fluctuations). Aging of the drifting plasma over a~24 h period led to an enhanced heavy ion content [Smith and Bewtra, 1978;Fok et al, 1991;Ebihara et al, 1998;Ferradas et al, 2015;Kistler and Mouikis, 2016]. This plasma mimics the presence of local in situ acceleration of the low-energy population.…”
Section: Discussionmentioning
confidence: 90%
“…Since O + is a major constituent of the ionosphere, and not of the solar wind, the presence of high-density O + (along with He + ) is strongly indicative of an ionospheric source. These losses result in changes in the composition that are energy (i.e., drift) dependent [Ferradas et al, 2015;Kistler and Mouikis, 2016]. (a) Direct and local acceleration of ionosphere and/or plasmasphere ions.…”
Section: Introductionmentioning
confidence: 99%
“…While H + and O + pressures are similar further out, at lower L values the O + pressure is about double the H + pressure at its peak. Previous work [ Lundin et al ., ; Ferradas et al ., ] has shown that charge exchange can lead to O + dominance inside L = 4 during quiet times because the charge exchange rate for H + is higher than O + for energies less than 45 keV. However, during storm times, the convection is faster, so charge exchange only significantly impacts the lowest L values.…”
Section: Discussionmentioning
confidence: 99%
“…They decreased down to <1 at the inner edge (Lm~2). The high ratios seemingly spatially localized in the radial direction are beyond the scope of this paper; it is probably related to the events observed by Cluster at its perigees (Ferradas et al, 2015) and by Van Allen Probes (Zhao et al, 2015) and will be investigated in near future with a larger database of MEP-i observations. The He+ energy density was more than 1 order of magnitude lower through all L shell ranges.…”
Section: 1029/2018gl080047mentioning
confidence: 95%